Academic Integrity in Student Research: A Review of Plagiarism Causes and Practical and Policy Implications - Cromwell F Gopo (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This review examined academic integrity in student research by synthesizing evidence on the causes of plagiarism, its practical implications, and the policy implications for educational institutions. Specifically, the study explored the factors influencing plagiarism among students and identified institutional and instructional interventions that promote ethical research practices. Methodology: This study employed a literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 37 studies published between 2000 and 2022 were analyzed to determine the reasons students commit plagiarism in research and the strategies used to prevent academic dishonesty. Relevant articles were retrieved through Scopus, Web of Science, Google Scholar, Semantic Scholar, ERIC, and OpenAlex exported to EndNote for organization, screened for duplicates, and evaluated for relevance prior to thematic analysis. Main Findings: The literature shows that plagiarism in student research is mainly caused by (1) weak research competencies such as poor writing, limited understanding of plagiarism, and incorrect referencing, (2) easy internet access including copy–paste practices and paper mills, (3) negative student attitudes such as peer influence, time pressure, desire for high grades, and low writing confidence, and (4) weak school enforcement and supervision. To address this, teachers and lecturers are encouraged to strengthen instruction in research skills and citation, integrate plagiarism awareness into the curriculum, use plagiarism detection tools, and improve students’ technical writing and time management through structured guidance and collaboration. At the institutional level, effective prevention requires clear policies with consistent sanctions for academic dishonesty alongside ethics education and reinforcement of academic integrity to ensure authentic student outputs and reliable assessment outcomes. Novelty/Originality of this study: This study is novel in its PRISMA-based synthesis of 37 studies that integrates the causes, interventions, and institutional policies on plagiarism in student research into a single multi-level framework. It is also original in linking plagiarism to the validity of educational assessment systems, emphasizing its impact on grading accuracy, academic integrity, and institutional accountability.